The "tone effect" of news on investor beliefs: An experimental approach - Ronald Bosman; Roman Kräussl; Elizaveta Mirgorodskaya (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We investigate the effect of the tone of news on investor stock price expectations and beliefs. In an experimental study we ask subjects to estimate a future stock price for twelve real listed companies. As additional information we provide them with historical stock prices and extracts from real newspaper articles. We propose a way to manipulate the tone of news extracts without distorting its content. Subjects in different treatment groups read news items that are written either in positive or negative tone for each stock. We find that subjects tend to predict a significantly higher (lower) return for stocks after reading positive (negative) tone news. The effect is especially pronounced for stocks with poor past performance. Subjects are more likely to be optimistic (pessimistic) about the economy and to buy (sell) stocks after reading positive (negative) than negative (positive) tone news. Our results show that the news media might affect not only how investors perceive information, but also what they do in response to it.
urn:nbn:de:hebis:30:3-386632
Keywords: D83; G02; G11; 330; Tone; News; Framing Effect; Price Expectations; Investor Sentiment; Investment Decisions; Experiment